Introduction: Special Issue on Indigenous Early Parenthood - Castellano, Marlene Brant (International Indigenous Policy Journal, 2013)
This introduction underscores many of the points raised and facts presented in the articles of this special edition of the International Indigenous Policy Journal on Indigenous Early Parenthood. It briefly mentions the interrelationship between economic deprivation and high fertility rates among Canada’s First Nations populations as well as the challenges and consequences of early parenting. While the authors may not make policy prescriptions, they emphasize the need for young parents and their children to receive the supports needed to help break the cycle of negative outcomes, which can be achieved through education, protection, and actualizing the value of ensuring that every child is a welcome and sacred gift.